Relevance of smartwatch use for detecting and monitoring atrial fibrillation: a systematic mapping (Research, Society and Development, 2022)
Given the expansion of digital devices to monitor vital signs aiming at quality of life - e-health -, the aim of this study was to conduct a literature review that sought to understand the relevance of the use of smartwatch for detecting and monitoring vital signs that trigger atrial fibrillation (AF), a common but difficult to diagnose heart disease in the world population. From search definitions, at the end, 7 articles were reserved for analysis. The reserved articles were taken from the Virtual Health Library, Science Direct, and Scopus databases from 2019 to 2022. The studies occurred in hospitals located in China, the United States, Belgium, Australia, Taiwan, Germany, and Switzerland, with male (55,8%) and female (44,2%) participants, aged 43 to 91 years. Vital signs were measured using smartwatches from Apple, Samsung, Garmin, Amazfit, Wavelet, and Huawei. For double-checking the signals, electrocardiograms of 1, 7, and 12 leads were used. When compiling the quantitative parameters, the overall average of sensitivity, specificity, positive predictive value, negative predictive value, and accuracy were 96,29%, 94,25%, 87,44%, 97,28%, and 94,73%, respectively. The results presented were promising in understanding how useful smartwatch can be used as an auxiliary tool for patients with AF.